The comparison of transvaginal ultrasonography and hysteroscopy in women with abnormal uterine bleeding: A single center experience (Annals of Medical Research, 2021)
None
Keywords: Abnormal uterine bleeding; endometrial fibroid; endometrial polyp; hysteroscopy; ultrasound.